Wordwall Assisted Online Learning Evaluation Training as an Innovative Formulation for Elementary School Teachers During the Pandemic - Meidawati Suswandari; Para Mitta Purbosari; Yohanes Sugiyanto; Annisa Muthmainnah (STKIP Singkawang, 2022)
Learning evaluations that include the game process in it can make students comfortable and feel good about working on questions. So far, it is still with evaluations that are not inserted with interesting content and variations when students work on questions. The wordwall application can be used as an evaluation of innovative learning at SD N Buran 03, Karanganyar. The wordwall evaluation training aims to make teachers more innovative in evaluating the learning given to students so that it is easier to measure the learning process. This training method is carried out in 4 stages, namely the socialization stage, the training stage, the monitoring stage, and the evaluation stage. The training participants consisted of school principals, class teachers, librarians, and 12 employees. The results of this training show that the trainees are enthusiastic and able to implement the preparation of wordwall-assisted learning evaluations. This can be seen from the percentage of success of the trainees who have evaluated the wordwall learning well and smoothly. Similarly, the posttest results stated that there was a satisfaction index of 7 people in wordwall training (58%), a usefulness index in the Very Useful category of 9 people (75%), and the sustainability of training activities 7 people (58%)..